2023
DOI: 10.5607/en23014
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Amyloid-β Clearance in the Brain and Periphery: Implications for Neurodegenerative Diseases

Rahat Ullah,
Eun Jeong Lee

Abstract: This review examines the role of impaired amyloid-β clearance in the accumulation of amyloid-β in the brain and the periphery, which is closely associated with Alzheimer's disease (AD) and cerebral amyloid angiopathy (CAA). The molecular mechanism underlying amyloid-β accumulation is largely unknown, but recent evidence suggests that impaired amyloid-β clearance plays a critical role in its accumulation. The review provides an overview of recent research and proposes strategies for efficient amyloid-β clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 342 publications
1
4
0
Order By: Relevance
“…[5][6][7][8][9] However, this risk is thought to be low because multiple other enzymatic pathways and transport proteins are involved in the clearance of Aβ peptides in the brain. [10][11][12] Moreover, the incidence of dementia-related adverse events (AEs) in patients treated with sacubitril/valsartan was similar to the incidence in patients treated with enalapril in PARADIGM-HF (Prospective Comparison of ARNi With ACEi to Determine Impact on Global Mortality and Morbidity in Heart Failure) and similar to the rate observed in patients enrolled in other trials enrolling patients with heart failure with reduced ejection fraction. 13 However, the patients in PARADIGM-HF were relatively young (age being an important risk factor for cognitive decline), and followup was relatively short (longer exposure is more likely to show an effect of treatment).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…[5][6][7][8][9] However, this risk is thought to be low because multiple other enzymatic pathways and transport proteins are involved in the clearance of Aβ peptides in the brain. [10][11][12] Moreover, the incidence of dementia-related adverse events (AEs) in patients treated with sacubitril/valsartan was similar to the incidence in patients treated with enalapril in PARADIGM-HF (Prospective Comparison of ARNi With ACEi to Determine Impact on Global Mortality and Morbidity in Heart Failure) and similar to the rate observed in patients enrolled in other trials enrolling patients with heart failure with reduced ejection fraction. 13 However, the patients in PARADIGM-HF were relatively young (age being an important risk factor for cognitive decline), and followup was relatively short (longer exposure is more likely to show an effect of treatment).…”
supporting
confidence: 65%
“…[5][6][7][8][9] This view is also consistent with the finding that sacubitril/valsartan did not increase the concentration of amyloidogenic species in the cerebrospinal fluid of healthy volunteers or brain tissue in cynomolgus monkeys and the evidence that multiple other pathways are also responsible for the clearance of neurotoxic Aβ peptides from the central nervous system. [10][11][12][41][42][43] In addition, a recent study showed that, in patients with a history of myocardial infarction, treatment with sacubitril/valsartan compared with valsartan increased both circulating Aβ42 and Aβ40 (with a reduction in the β42/Aβ40 ratio), a pattern that differs from Alzheimer disease in which the Aβ42/Aβ40 ratio is reduced, because of a pathological decrease in Aβ42 but unchanged Aβ40. Circulating biomarkers of phosphorylated tau and glial fibrillary acidic protein, associated with Aβ and tau neuropathology and predictive of cognitive decline, and neurofilament light, associated with neuronal injury, did not differ between treatments.…”
Section: Dementia During Follow-upmentioning
confidence: 99%
“…[ 26 ] Our data show that at least at the RNA level LRP‐1 is not affected in pediatric patients with hepatic fibrosis (Figure 2F ). However, acknowledging the existence of a great variety of other Aβ transporters and Aβ‐binding proteins in the blood, [ 27 ] the extent to which changes in transporter systems contribute to the hepatic content of Aβ and the progression of fibrosis remains a subject for future investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Early-onset forms of AD are thought to arise from the increased production of Aβ, while late-onset forms stem from reduced Aβ clearance [254,255]. This clearance occurs through both enzymatic and non-enzymatic processes (reviewed in [256]).…”
Section: Aβ Clearancementioning
confidence: 99%
“…In the brain, Aβ is primarily degraded and cleared through the proteolytic machinery [257,258], and more than 20 different Aβ-degrading enzymes (ADEs) have been identified, including metallo-serine, aspartyl, cysteine, and threonine proteases [259]. To date, metalloproteases are the best studied ADEs, with matrix metalloprotease 2 (MMP2), MMP7, and MMP9 demonstrating Aβ-degrading activity and association with AD [256]. Tissue inhibitors of metalloproteases (TIMPs) regulate MMP activity [260] and have been linked to AD as well [137,[261][262][263].…”
Section: Aβ Clearancementioning
confidence: 99%